2018
DOI: 10.1021/acs.jafc.7b05123
|View full text |Cite
|
Sign up to set email alerts
|

Selection for Cd Pollution-Safe Cultivars of Chinese Kale (Brassica alboglabra L. H. Bailey) and Biochemical Mechanisms of the Cultivar-Dependent Cd Accumulation Involving in Cd Subcellular Distribution

Abstract: Two pot experiments were conducted to compare and verify Cd accumulation capacities of different cultivars under Cd exposures (0.215, 0.543, and 0.925 mg kg in Exp-1 and 0.143, 0.619, and 1.407 mg kg in Exp-2) and Cd subcellular distributions between low- and high-Cd cultivars. Shoot Cd concentrations between the selected low- and high-Cd cultivars were 1.4-fold different and the results were reproducible. The proportions of Cd-in-cell-wall of shoots and roots were all higher in a typical low-Cd cultivar (DX10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 41 publications
(95 reference statements)
3
45
0
Order By: Relevance
“…Interestingly, the study also showed increased uptake of cadmium in rice crops planted after the oilseed rape harvest, with contamination of rice higher compared to a crop after a fallow period. Another mechanism of plants which can be used advantageously is that of reduced accumulation of unwanted chemicals in certain cultivars or altered plant hybrids—for example in Chinese kale—and these can be selected to produce safer food [168].…”
Section: Remediationmentioning
confidence: 99%
“…Interestingly, the study also showed increased uptake of cadmium in rice crops planted after the oilseed rape harvest, with contamination of rice higher compared to a crop after a fallow period. Another mechanism of plants which can be used advantageously is that of reduced accumulation of unwanted chemicals in certain cultivars or altered plant hybrids—for example in Chinese kale—and these can be selected to produce safer food [168].…”
Section: Remediationmentioning
confidence: 99%
“…The subcellular distribution of Cd was measured using the method described by Guo et al (2018). The root, stem, and leaf tissues of each frozen sample were homogenized on ice in the presence of extraction buffer (50 mM Tris-HCl, 250 mM sucrose, 1.0 mM C 4 H 10 O 2 S 2 , and 5.0 mM ascorbic acid).…”
Section: Subcellular Distribution Of Cadmiummentioning
confidence: 99%
“…Biomass response to stress is a common method for detecting Cd tolerance in plants (Wang et al 2009;Guo et al 2018). In this study, two Cd concentrations were used: low-Cd (2.9 mg/kg) and high-Cd (4.7 mg/kg), which covered most of the concentration range of arable land Cd contamination in South China (He et al 2020;Mamat et al 2020).…”
Section: Differences In Cadmium Tolerance and Cadmium Accumulation Existed Among Eggplant Cultivarsmentioning
confidence: 99%
See 2 more Smart Citations